Go, Goofy, go! - Higginson, Sheila Sweeny, 1966-; Loter, Inc. (New York : Disney Press, 2008)
Goofy experiments with different ways to get to the clubhouse, then decides that walking is the simplest solution.
"A level 1 early reader.".
"Mickey Mouse Clubhouse.".
"With 12 flash cards!"--Cover.
1.8
K-3
Keywords: Goofy (Fictitious character) -- Juvenile fiction; Transportation -- Juvenile fiction; Walking -- Juvenile fiction; Goofy (Fictitious character) -- Fiction; Transportation -- Fiction; Walking -- Fiction; Goofy (Fictional character) -- Fiction; Transportation -- Fiction; Walking -- Fiction